1987
DOI: 10.1007/bf00156584
|View full text |Cite
|
Sign up to set email alerts
|

Myths and the definition of policy problems

Abstract: In this paper we argue that behind widely accepted problem definitions are myths, stories which draw on tradition and taken for granted knowledge. These myths, which may or may not be true in a factual sense, are important to the definition of problems because they link public issues to widely accepted ways of understanding the world and to shared moral evaluations of conditions, events, and possible solutions to problems.Such myths perform a double-edged function in a policy or planning process. On the one ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(9 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…de Neufville and Barton (1987) examine the central place of such narratives in the de nition of policy problems. They argue that narratives -in the sense of culturally shared and morally charged social meanings expressed in story form -comprise a vital component in the construction of social policy and in providing the "emotional charge" necessary for mobilising suf cient support for the implementation of particular kinds of social policy measures.…”
Section: Narratives That Underly Social Policies and Give Them Emotivmentioning
confidence: 99%
“…de Neufville and Barton (1987) examine the central place of such narratives in the de nition of policy problems. They argue that narratives -in the sense of culturally shared and morally charged social meanings expressed in story form -comprise a vital component in the construction of social policy and in providing the "emotional charge" necessary for mobilising suf cient support for the implementation of particular kinds of social policy measures.…”
Section: Narratives That Underly Social Policies and Give Them Emotivmentioning
confidence: 99%
“…4, pp. 70-91, janeiro/fevereiro, 2018 www.anpad.org.br/rac valores e ideias (Bottici & Challand, 2006;Esch, 2010), sendo criados na forma de um repertório de narrativas, imagens, símbolos e modos de ação (De Neufville & Barton, 1987).…”
Section: A Análise Retóricaunclassified
“…The principle is not confined to individual anecdotes or case studies, but has been borne out in econometric tests of the determinants of economic performance across a comprehensive sample of countries. '' Neufville and Stephen Barton's insightful ''Myths and the Definition of Policy Problems,'' focusing on how myths (in the sense of beliefs derived from tradition and culturally shared taken-for-granted knowledge, rather than false beliefs) skewed the problem definition of US housing policy through elevating home ownership as a sacrosanct objective (de Neufville and Barton 1987). Rosenman et al (1988) demonstrated the huge difference in the expected costs of nuclear waste disposal if the problem definition includes a more appropriate recognition of changes in levels of uncertainty.…”
Section: What We Rejectedmentioning
confidence: 99%